PERBANDINGAN INFORMASI CITRA ANATOMI MRA RENAL DENGAN MENGGUNAKAN METODE TIME OF FLIGHT DAN PHASE CONTRAST DI INSTALASI RADIOLOGI RSUD ARIFIN ACHMAD PROVINSI RIAU - Hadi Eka Hamdani Hadi; Eka Juliantara; Ni Nyoman Supriyani (Medical Imaging and Radiation Protection Research Journal, 2022)
Background: The hospital has standardized the selection of sequences used for MRA examination. In the Radiology Installation of Arifin Achmad Hospital, Riau Province, only one time of flight sequence was used from two non-contrast MRA sequences, namely time of flight and phase contrast. In this regard, there are two sequences of non-contrast MRA examination that need to be used in order to identify and produce a good image of the renal vessels. Methods: This study is a quantitative study with an experimental approach that aims to determine differences in information on anatomical MRA Renal images using 2 non-contrast MRA methods, namely time of flight and phase contrast. This study applies the Lemeshaw formula with a 95% confidence level, using 10 Renal MRA patients and 3 radiology specialists as respondents for image assessment. Results: The results showed that there was no difference between tof and pc sequences in the anatomy of the renal arteries and segmental arteries. However, there were significant differences shown in the anatomical assessments performed (interlobar arteries, arcate arteries, and interlobular arteries). Almost all indicators show a p-value of <0.050, with the 3d time of flight sequence showing superiority in all aspects assessed compared to the 3d phase contrast sequence. Conclusion: There is a difference in anatomical image information on the Renal MRA using 3d time of flight sequences and 3d phase contrast. In the 3d time of flight sequence, it is able to produce arterial images well but lacks in displaying venous images. On the other hand, the 3d time of flight sequence is good at showing veins and lacking in arterial imaging. Keywords: mra renal; time of flight; phase contrast